A novel bacterial cellulose membrane immobilized with human umbilical cord mesenchymal stem cells-derived exosome prevents epidural fibrosis - Wang B (Dove Medical Press, 2018)
Bo Wang,1,* Peng Li,1,* Lei Shangguan,2,* Jun Ma,3,* Kezheng Mao,4 Quan Zhang,5 Yiguo Wang,6 Zhongyang Liu,1,2 Keya Mao1 1Department of Orthopedics, Chinese PLA General Hospital, Beijing, 100853, China; 2Department of Orthopedics, Xijing Hospital, Fourth Military Medical University, Xi’an, Shaanxi, 710032, China; 3Department of Orthopedics Trauma Surgery, Changzheng Hospital, Second Military Medical University, Shanghai, 200003, China; 4Department of Orthopedics, Orthopedics Hospital of Zhengzhou City, Zhengzhou, Henan, 450052, China; 5Department of Orthopedics, People’s Hospital of Tianjin City, Tianjin, 300121, China; 6Department of Orthopedics, Second Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, 210000, China *These authors contributed equally to this work Introduction: Failed back surgery syndrome is a situation where there is failure after lumbar surgery aimed at correcting lumbar disease that is characterized by continuous back and/or leg pain. Epidural fibrosis and adhesions are among the major causes of failed back surgery syndrome. In recent years, several biomaterials have been applied as barriers or deterrents to prevent the compression of neural structures by postsurgical fibrosis. Methods: In this study, a new bacterial cellulose (BC) anti-adhesion membrane, composed of exosomes from human umbilical cord mesenchymal stem cells, was developed. Its structure and morphology, water content, thickness, and mechanical properties of elasticity were analyzed and characterized. The degradation of the BC+exosomes (BC+Exos) membrane in vitro was evaluated, and its in vitro cytotoxicity and in vivo biocompatibility were tested. The prevention effect of BC+Exos membrane on epidural fibrosis post-laminectomy in a rabbit model was investigated. Results: The BC+Exos membrane showed a three-dimensional network structure constituted of high-purity cellulose and moderate mechanical properties. No degeneration was observed. The BC+Exos membrane showed no cytotoxicity and displayed biocompatibility in vivo. The BC+Exos film was able to inhibit epidural fibrosis and peridural adhesions. Conclusion: Based on the current findings, the BC+Exos membrane is a promising material to prevent postoperative epidural fibrosis and adhesion. Keywords: failed back surgery syndrome, epidural fibrosis, adhesion, human umbilical cord mesenchymal stem cell, exosome, bacterial cellulose